The Effect of Product Reviews and Endorsements by Beauty Influencers on Skincare Purchase Intention (Study on Students of Muhammadiyah University of North Sumatra) - Nadia Ika Purnama; Hanny Alvi Sahrina Hrp; Muhammad Andi Prayogi (Apollo: Journal of Tourism and Business, 2026)
This study examines the effect of product reviews and beauty influencer endorsements on skincare purchase intention among students of Muhammadiyah University of North Sumatra. The problem in this study is that consumer purchase intention toward skincare products is still not optimal despite the increasing number of product reviews and influencer endorsements on social media platforms. Product reviews are often perceived as repetitive, overly promotional, and lacking authenticity, while endorsements by beauty influencers are sometimes considered less credible due to excessive commercial motives. This study aims to determine and analyze the effect of product reviews and beauty influencer endorsements on purchase intention both partially and simultaneously. This research uses a quantitative associative approach. The sampling technique applies the Lemeshow formula with a total sample of 100 respondents. Data were collected using questionnaires with a Likert scale. Data analysis techniques include validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and coefficient of determination tests using SPSS. The results show that product reviews have a positive and significant effect on purchase intention, endorsements also have a positive and significant effect on purchase intention, and both variables simultaneously have a positive and significant effect on purchase intention. The Adjusted R Square value of 0.405 indicates that 40.5% of purchase intention is explained by product reviews and endorsements, while the remaining 59.5% is influenced by other variables outside this study.